Surface Passivation of Nanoporous TiO2 via Atomic Layer Deposition of ZrO2 for Solid-State Dye-Sensitized Solar Cell Applications - Li, Tina C.; Goes, Marcio S. [UNESP]; Fabregat-Santiago, Francisco; Bisquert, Juan; Bueno, Paulo Roberto [UNESP]; Prasittichai, Chaiya; Hupp, Joseph T.; Marks, Tobin J. (Amer Chemical Soc, 2009)
We report here the utilization of atomid layer deposition to passivate surface map states in mosoporous TiO2 nanoparticles for solid state dye sensitized solar cells based on 9,9'-spirobifluorene (spiro-OMeTAD). By depositing ZrO2 films with angstrom-level precision, coating the mesoporous TiO2 produces over a two-fold enhancement in short-circuit current density, as compared to a control device. Impedance spectroscopy measurements provide evidence that the ZrO2 coating reduces recombination lossed at the TiO2/spiro-OMeTAD interface and passivates localized surface states. Low-frequency negative capacitances, frequently observed in nanocomposite solar cells, have been associated with the surface-state mediated charge transfer from TiO2 to the spiro-OMeTAD.